2009
DOI: 10.1016/j.jtcvs.2008.09.080
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgical ablation of atrial fibrillation: Six-month results

Abstract: Minimally invasive atrial fibrillation surgery is an effective treatment of paroxysmal atrial fibrillation at 6 months. Continuous event monitoring is necessary to accurately assess treatment results. A more extensive lesion set seems to be required for treatment of persistent atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 25 publications
0
60
0
1
Order By: Relevance
“…A second, larger report from this group in 114 patients reported that 72%, 46.9%, and 32% of patients with paroxysmal, persistent, and long-standing persistent AF, respectively, were free of AF and off antiarrhythmic medications at 195 days of follow-up. 1355 Another multi-center series of 100 patients with a similar approach and mean follow-up of 13.6 months reported a sinus restoration rate of 87%, with 64% of patients free from AADs. 1356 The results of these and other trials cited earlier in this section have made it clear that a more extensive lesion set than PVI alone is required for successful surgical treatment of persistent and long-standing persistent AF.…”
Section: Stand-alone Surgical Ablation Of Afmentioning
confidence: 98%
See 1 more Smart Citation
“…A second, larger report from this group in 114 patients reported that 72%, 46.9%, and 32% of patients with paroxysmal, persistent, and long-standing persistent AF, respectively, were free of AF and off antiarrhythmic medications at 195 days of follow-up. 1355 Another multi-center series of 100 patients with a similar approach and mean follow-up of 13.6 months reported a sinus restoration rate of 87%, with 64% of patients free from AADs. 1356 The results of these and other trials cited earlier in this section have made it clear that a more extensive lesion set than PVI alone is required for successful surgical treatment of persistent and long-standing persistent AF.…”
Section: Stand-alone Surgical Ablation Of Afmentioning
confidence: 98%
“…197,1369,1370,1371 However, investigators showed that this treatment was inadequate for patients with persistent and long-standing persistent AF. 1355 This led to the belief that the persistent forms of AF needed both substrate modification and trigger isolation , and this provided the impetus to develop the Dallas lesion set, which replicated all the LA lesions of the Cox-Maze III, yet allowed them to be placed on the surface of the full-beating LA. Although it was a major step forward, with a success rate of 79%, this approach failed to reach the success rates of the Cox-Maze III.…”
Section: Stand-alone Surgical Ablation Of Afmentioning
confidence: 99%
“…Another study with 114 patients published that 46.9% and 32% of patients with persistent and longstanding persistent AF were free of AF and off antiarrhythmic medications at 195 days of follow-up [22]. After thoracoscopic offpump radiofrequency pulmonary vein isolation plus left atrial appendage exclusion 60% to 80% of patients obtain sinus rhythm [23][24][25][26].…”
Section: Thoracoscopic Epicardial Posterior Left Atrial Wall Isolatiomentioning
confidence: 99%
“…Durch Einsatz des neuen, rein thorakoskopischen bipolaren Ablationsverfahrens gelingt eine Substratmodifikation des linken Vorhofs mit zusĂ€tzlicher Entfernung des linken Vorhofohrs [32,33]. Mittels Einbringen von jeweils 3 Ports in beide ThoraxhĂ€lften und Insufflation von CO 2 können nach Eröffnen des Perikards beide Pulmonalvenenpaare, durch Herstellen einer "box lesion" das Antrum des linken Vorhofs und durch eine lineare Ablationslinie im Bereich des linken Vorhofdachs der linksatriale Isthmus abladiert werden (.…”
Section: Bipolare Hochfrequenzenergieunclassified